Strength training and metabolic conditioning for female youth and adolescent soccer players. - Wright, M. D.; Laas, M.-M. (Strength and Conditioning Journal, 2016)
Despite the rapid growth in women and girls playing soccer, evidence-based guidelines to inform conditioning for girls are sparse. Most research on youth soccer is conducted in males, which may not be transferable to practice in female teams. This article reflects on the current evidence base and draws on the authors' experiences to provide guidelines to improve conditioning programs throughout maturation in girls. The article focuses on the integration of neuromuscular and metabolic conditioning methods to safely improve physical performance and reduce injury risk factors. Guidelines are presented for players pre, circum, and post peak height velocity.